PERHITUNGAN BIAYA MODAL UNTUK MENGANALISIS KINERJA KEUANGAN - Miske Wananda; Mahdi Hendrich; Farida Husin (Politeknik Negeri Sriwijaya, 2021)
This study aims to determine the rate of return that a company must achieve on investment to maintain its stock market value. The results of this study indicate that the company's capital structure is less than optimal because the optimal capital structure is a capital structure that minimizes the weighted average cost of capital (WACC). From the results of the analysis and discussion conducted that PT. Mayora Indah, Tbk obtained WACC values of 32.25%, 39.61%, 74.83%, 65.13%, and 74.62%. The WACC value that has the best performance and provides the minimum rate of return indicated by investors is in the 2015 period. This calculation of the cost of capital can be used as a reference by company management to pay attention to the composition of the company's capital structure by reducing funding through debt to reduce financial risk and company capital costs.